Flooding the Brains: Natural Disasters, Student Outcomes, and the Urban-Rural Gap in Human Capital - Juan S. Mu\~noz-Morales (Institute of Labor Economics (IZA), 2024)
This study provides evidence that natural disasters negatively affect student outcomes, potentially explaining the lower academic achievement of students in rural areas compared to their urban counterparts in developing countries. Using data from the Colombian school census, I estimate a difference-in-differences strategy that exploits variation from an unusual rainfall shock affecting over two million people in both urban and rural Colombia. The results show that these disruptions increase school dropout rates and reduce learning outcomes for at least a decade. The effects are concentrated in rural schools, while students in urban schools remain unaffected. I explore several mechanisms and rule out the possibility that the effects are driven by selective migration or a loss of educational resources. Instead, I find evidence that the rainfall shock exacerbated poverty, pushing poorer rural children into unemployment and longer work hours.
Keywords: I24; I25; R11; 330; natural disasters; human capital; education; urban-rural gap; Colombia